Multi-agent-based control strategy for centerless energy management in microgrid clusters - Shi, Shuang; Wang, Yanping; Jin, Jiyu (Frontiers in Energy Research, 2023)
Interconnecting microgrids with similar geographical environment and related characteristics electrically and communicatively, this constitutes a microgrid cluster, which is a higher-level distributed power structure and an effective way to improve the utilization rate of distributed energy and local absorption level. However, the stable operation of microgrid clusters is determined by the cluster structure and its control strategy, which is also the focus and difficulty of current research. To address this challenge, this paper proposes a ring-based multi-agent microgrid cluster energy management strategy, which realizes the centerless coordinated autonomous operation of microgrid clusters with high stability. In addition, based on the multi-agent control strategy, this paper designs a variety of control strategies that can be switched autonomously for different control objectives of the microgrid cluster to realize smooth grid connection and off-grid of the microgrid cluster. Finally, based on Matlab platform simulation, the experimental results show that the control structure and energy management strategy proposed in this paper can realize the centerless coordination and autonomy of the microgrid cluster on the basis of stable operation, minimize the energy interaction between the cluster and the distribution network, and greatly improve the utilization rate and local absorption level of distributed energy.